Kinematic measurement of wheelchair racing using smartphones sensors - Ming, Chow Kin (2019)
Givem the increasing demand for high-performance in Paralympic sports, there is likewise as larger demand for analytical data. Recent developments in miniaturisation allows tri-axial measurement of the accelarartion with very small sensores (~2.6mm3) such as the ones embebed in smartphones.